Prevalence, incidence, and reported global distribution of noma: a systematic literature review. Issue 8 (August 2022) - Galli, Anaïs; Brugger, Curdin; Fürst, Thomas; Monnier, Nora; Winkler, Mirko S; Steinmann, Peter
Summary: Noma ( cancrum oris ) is a severely debilitating orofacial disease. The global annual incidence and prevalence figures of noma are outdated and were not based on epidemiological studies. Therefore, we systematically reviewed the scientific literature about the prevalence, incidence, and reported global distribution of noma. We searched ten databases and Google Scholar from 1950 up to Sept 23, 2020. We used an adapted Newcastle–Ottawa scale for quality assessment of the studies we included. Epidemiological data could be extracted from eight publications. Because of the differences in quality and the limited geographical range of the studies, no new estimate of the global incidence and prevalence of noma could be calculated. Our updated world map indicates that patients with noma were diagnosed in at least 23 countries in the past decade. Additionally, we identified a strong focality, with most cases being reported from only a few countries in west Africa. This systematic review has identified a striking scarcity of research and surveillance programmes considering noma. We argue that a first step to noma elimination should be the inclusion of noma in the WHO list of neglected tropical diseases, followed by broad-based integrated control programmes aiming at noma elimination.